3D-Cultivation of bone marrow stromal cells on hydroxyapatite scaffolds fabricated by dispense-plotting and negative mould technique - Detsch, Rainer; et al. (Journal of Materials Science: Materials in Medicine, 2008)
The main principle of a bone tissue engineering (BTE) strategy is to cultivate osteogenic cells in an osteoconductive porous scaffold. Ceramic implants for osteogenesis are based mainly on hydroxyapatite (HA), since this is the inorganic component of bone. Rapid Prototyping (RP) is a new technology in research for producing ceramic scaffolds. This technology is particularly suitable for the fabrication of individually and specially tailored single implants. For tissue engineering these scaffolds are seeded with osteoblast or osteoblast precursor cells. To supply the cultured osteoblastic cells efficiently with nutrition in these 3D-geometries a bioreactor system can be used. The aim of this study was to analyse the influence of differently fabricated HA-scaffolds on bone marrow stromal cells. For this, two RP-techniques, dispense-plotting and a negative mould method, were used to produce porous ceramics. The manufactured HA-scaffolds were then cultivated in a dynamic system (bioreactor) with an osteoblastic precursor cell line. In our study, the applied RP-techniques give the opportunity to design and process HA-scaffolds with defined porosity, interconnectivity and 3D pore distribution. A higher differentiation of bone marrow stromal cells could be detected on the negative mould fabricated scaffolds, while cell proliferation was higher on the dispense-plotted scaffolds. Nevertheless, both scaffold types can be used in tissue engineering applications. © 2007 Springer Science+Business Media, LLC.